Bimbingan Kelompok Teknik Diskusi Buzz Group untuk Meningkatkan Kemampuan Mengemukakan Pendapat - Eva Fitriyani; Sri Wiyanti; Ulya Makhmudah (Jurnal Psikoedukasi dan Konseling, 2022)
Abstract: The purpose of this study was to determine the effectiveness of the group guidance of the buzz group discussion technique to improve the ability to express opinions. This research is experimental research with Quasi-Experimental Design. Students as research subjects who can express low opinions obtained from the pretest results. The research subjects were divided into two groups, namely the experimental group and the control group. The experimental group was given treatment in the form of group guidance on buzz group discussion techniques to improve the ability to express opinions, and the control group was not given treatment. The analysis used the MannWhitney technique obtained Z of -4,984 with p value 0,000 (0,000 <0,05), meaning that there is a difference in the results of the experimental group with the control group, which shows an increase in the score in the experimental group after being given treatment. In addition, the Wilcoxon technical analysis showed Z of -3,624 with a significance value of 0,000, then 0,000 <0,05, meaning that there was an increase in the posttest score in the experimental group after being given treatment in the form of group guidance on the buzz group discussion technique. Based on the analysis results, it was concluded that the group guidance of the buzz group discussion technique effectively improved the ability to express opinions.